1993
DOI: 10.1177/00220345930720060201
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Titanium and Hydroxyapatite on Osteoblastic Expression and Proliferation in Rat Parietal Bone Cultures

Abstract: Titanium and hydroxyapatite are used for the fabrication of dental and orthopedic implants. The longevity of these implants depends on the amount and rate of bone formation that occurs around their surfaces. In the present study, the effects of titanium, hydroxyapatite, and polystyrene (control) on the proliferation of rat calvarial cells, and on their capacity to express alkaline phosphatase and respond to parathyroid hormone (PTH) stimulation, were studied. The nature of the substrate did not affect the DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 11 publications
2
37
0
1
Order By: Relevance
“…Massas et al 10 studied the effects of titanium, hydroxyapatite, and polystyrene (control) on the proliferation of rat calvarial cells and on the capacity to express alkaline phosphatase and to respond to parathyroid hormone stimulation. These authors reported that the nature of the substrate did not affect the DNA and protein contents of experimental and control cultures throughout the experimental period.…”
Section: Introductionmentioning
confidence: 99%
“…Massas et al 10 studied the effects of titanium, hydroxyapatite, and polystyrene (control) on the proliferation of rat calvarial cells and on the capacity to express alkaline phosphatase and to respond to parathyroid hormone stimulation. These authors reported that the nature of the substrate did not affect the DNA and protein contents of experimental and control cultures throughout the experimental period.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoblasts cultured on HA-coated Ti showed high differentiation and mineralization compared with non-coated Ti 32,33) . Expression of ALP and parathyroid hormone response were higher in cultures grown on HA than in cultures grown on Ti 34) , and the in vitro formation of extracellular matrices was greater on CaP coatings than on Ti. Several mechanisms have been suggested to underlie osteogenesis on CaP ceramics.…”
Section: Discussionmentioning
confidence: 91%
“…Alkaline phosphatase expression and parathyroid hormone response were higher in cultures grown in HA than in cultures grown in titanium, 12) and the in vitro formation of extracellular matrices was greater on Ca-P coatings than on titanium. Several mechanisms of the principal factors involved in osteogenesis on Ca-P ceramics have been considered.…”
Section: Surface Modifications Of Titanium With a Thin Cal-mentioning
confidence: 89%